Adrift: Attribution & Responsibility in a Changing Climate - Adam Sébire (Flugschriften, 2019)
What if we could witness our own contribution to the warming climate? And how do we know if we’re seeing the "fingerprints" of anthropogenic global warming on an event? Climate change event attribution is a relatively new field of enquiry. Borrowing a formula from climate scientists Notz & Stroeve, visual artist and PhD student Adam Sébire describes how he was able to calculate and saw off exactly the amount of Greenlandic sea-ice that would be destroyed by his carbon emissions flying economy return from Sydney to document it. The multiscreen video artwork created, AnthropoScene IV: Adrift (∆Asea-ice) (2019) touches upon the disconnects that underly our psychological response to climate change.